Implication of antithrombotic agents on potential bleeding from endoscopically determined peptic ulcers, incidentally detected as surrogate markers for nsaids‐associated ulcers complication. Issue 1 (11th June 2012) - Miyake, Kazumasa; Kusunoki, Masafumi; Ueki, Nobue; Nagoya, Hiroyuki; Kodaka, Yasuhiro; Shindo, Tomotaka; Kawagoe, Tetsuro; Gudis, Katya; Futagami, Seiji; Tsukui, Taku; Nakamura, Hiroshi; Sakamoto, Choitsu
Abstract : Background and aim: Little is known about the clinical significance of treatment for endoscopically determined peptic ulcers (EPU), incidentally detected as surrogate endpoints for non‐steroidal anti‐inflammatory drugs (NSAIDs)‐associated ulcers complication, such as overt bleeding and perforation. Even uncomplicated‐EPU without overt bleeding signs when antithrombotic agents (AT) were cotherapied may be of potential bleeding sites. The aim of the present study was to evaluate whether microcytic anemia, implying potential bleeding, is associated with NSAIDs‐associated EPU or cotherapies with AT. Methods: Two hundred and thirty‐eight outpatients with rheumatoid arthritis under long‐term NSAIDs therapies underwent upper endoscopy and were divided into the following four groups according to the pattern (presence: + or absence: –) of AT cotherapy/EPU, respectively: A, –/– ( n  = 165); B, –/+ ( n  = 44); C, +/– ( n  = 25); and D, +/+ ( n  = 4). Results: EPU were found in 48 of the 238 studied patients (20.2%). After significant interactions among four groups hadstatistically been identified, hemoglobin (Hb) and mean corpuscular volume (MCV) as biomarkers for potential bleeding were compared between the groups.Hb and MCV were significantly lower in the D group than in the A, B, or C groups (Hb: P  < 0.01, respectively; P  < 0.05, MCV; P  < 0.01 or P  < 0.05, respectively). Conclusions: Patients with NSAIDs‐associated EPU and AT cotherapy indicated significantly more severe microcytic anemia pattern than those without EPU or AT cotherapy, despite no evidence of overt bleeding. Even uncomplicated‐EPU without overt bleeding when ATs were cotherapied may be of potential bleeding sites.